The Economics of Gender-Specific Minimum Wage Legislation - Riccardo Marchingiglio; Mikhail Poyker (Institute of Labor Economics (IZA), 2024)
Using full count U.S. census data, we study the impact of early 20th-century state-industry-specific minimum wage laws that primarily targeted female employees. Our triple-difference estimates suggest a null impact of the minimum wage laws, potentially reflecting disemployment effects and the positive selection bias of the workers remaining in the labor force. When comparing county-industry trends between counties straddling state borders, female employment is lower by around 3.1% in affected county-industry cells. We further investigate the implications for own-wage elasticity of labor demand as a function of cross-industry concentration, the channels of substitution between men and women, and heterogeneity by marital status.
Keywords: J16; J23; N32; 330; minimum wage; labor demand; gender gap; labor markets